2014
DOI: 10.1016/j.jenvrad.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Abatement of xenon and iodine emissions from medical isotope production facilities

Abstract: The capability of the International Monitoring System (IMS) to detect xenon from underground nuclear explosions is dependent on the radioactive xenon background. Adding to the background, medical isotope production (MIP) by fission releases several important xenon isotopes including xenon-133 and iodine-133 that decays to xenon-133. The amount of xenon released from these facilities may be equivalent to or exceed that released from an underground nuclear explosion. Thus the release of gaseous fission products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The growing amount of radionuclides and radioactive wastes from various nuclear and medical fields is causing public concern due to their short- and long-term radiotoxic impact on nature1234. In particular, the anthropogenic radioiodine that has been released into nature for decades has become a key issue due to its global recycling567, which affects the worldwide ecosystem and human health89.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The growing amount of radionuclides and radioactive wastes from various nuclear and medical fields is causing public concern due to their short- and long-term radiotoxic impact on nature1234. In particular, the anthropogenic radioiodine that has been released into nature for decades has become a key issue due to its global recycling567, which affects the worldwide ecosystem and human health89.…”
mentioning
confidence: 99%
“…In particular, the anthropogenic radioiodine that has been released into nature for decades has become a key issue due to its global recycling567, which affects the worldwide ecosystem and human health89. Anthropogenic iodine radioisotopes mainly originate from human activities that are performed in the nuclear, industrial, and medical fields12389. The radioisotopes are damaging to human health because of their active participation in human metabolic processes.…”
mentioning
confidence: 99%
“…Activated carbon (AC) is used worldwide as an effective sorbent due to its high surface area and pore size. The capacity of AC can be enhanced by several techniques such as the selection of raw materials (coal, bamboo, coconut and walnut shells) used to synthesize the AC, method of preparation and activation, and impregnation of other compounds and entities (triethylenediamine TEDA and silver), changing functional group and phenolic group [35][36][37][38][39]. Park et al [35,36] reported on the adsorption of methyl iodide on AC and TEDAimpregnated AC in a continuous gas phase system.…”
Section: Capture Of Radioactive Contaminants By Dry Processes (Adsorpmentioning
confidence: 99%
“…The direct method was conducted by direct measurement of the 131 I air concentration from the stack with an LaBr3 (lanthanum (III) bromide) scintillation detector. The indirect method was performed by using activated charcoal filter (charcoal) [15,16]. The concentration of 131 I adsorbed in the charcoal was detected by scintillation detector of NaI(Tl) in a research laboratory.…”
Section: Monitor Calibration Of 131 I Radioactive Gasmentioning
confidence: 99%
“…Efficiency calibration was conducted by converting the measurement results of the count rate of radiation standard sources in counts per second (cps) to the activity in becquerels (Bq). The counting efficiency of the LaBr3 detector was calculated using equation (1) [16]:…”
Section: Monitor Calibration Of 131 I Radioactive Gasmentioning
confidence: 99%